antiCODE: a natural sense-antisense transcripts database - Liu Changning; Wang Jie; Zhao Yi; Yin Yifei; Chen Shuguang; Chen Runsheng; Zhao Haitao (BMC Bioinformatics, 2007)
Abstract Background Natural antisense transcripts (NATs) are endogenous RNA molecules that exhibit partial or complete complementarity to other RNAs, and that may contribute to the regulation of molecular functions at various levels. In recent years, large-scale NAT screens in several model organisms have produced much data, but there is no database to assemble all these data. AntiCODE intends to function as an integrated NAT database for this purpose. Results This release of antiCODE contains more than 30,000 non-redundant natural sense-antisense transcript pairs from 12 eukaryotic model organisms. In order to provide an integrated NAT research platform, efficient browser, search and Blast functions have been included to enable users to easily access information through parameters such as species, accession number, overlapping patterns, coding potential etc. In addition to the collected information, antiCODE also introduces a simple classification system to facilitate the study of natural antisense transcripts. Conclusion Though a few similar databases also dealing with NATs have appeared lately, antiCODE is the most comprehensive among these, comprising almost all currently detected NAT pairs.